Exploring Youths' Intention to Use Social Media Networks for Donation Online Campaigns Using TikTok - Khairani Azizah Novrin (International Journal of Zakat, 2025)
The digital era continues to innovate to provide new breakthroughs in the world of technology. The number of social media platforms in fact makes people increasingly curious about using them, one of which is the TikTok application. In fact, Indonesia is listed as the largest Tiktok user in the world with 157, 6 users. This certainly attracts the interest of various groups, especially marketing media. Currently, there are many social media that can be used not only as entertainment but also as a place to raise donations. This study investigates young people's behavioral intentions in making decisions to donate through the TikTok platform. Not only that, this can be used by institutions as a reference in developing donation collection to be more optimal, especially on the TikTok platform. This research uses a qualitative method obtained through distributing questionnaires dominated by young people. From these results, it can be analyzed that many young people's decisions to donate online are due to the emotional influence that exists in themselves to contribute to donations. It is hoped that this research can help improve zakat institutions in reaching donations using TikTok and increase the contribution of young people to participate in social care to achieve mutual prosperity